2001
DOI: 10.1046/j.1460-9592.2001.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

When Should Heparin Preferably Be Administered During Radiofrequency Catheter Ablation?

Abstract: RF catheter ablation is complicated by thromboembolism in about 1% of patients. Limited knowledge exists concerning when and how to use anticoagulation or antithrombotic treatment. We studied the activation of coagulation (prothrombin fragment 1 + 2 [PF1 + 2] and D-dimer), platelets (beta-thromboglobulin [beta-TG]) and fibrinolysis (plasmin-antiplasmin complexes [PAP]) during RF ablation of accessory pathways in 30 patients. They were randomized to receive heparin (100 IU/kg, intravenously) (1) immediately aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 0 publications
2
30
0
1
Order By: Relevance
“…The hemostasis that occurs with the placement of catheters has been described, 6,7,16,17 with some investigators correlating it with the duration of the pre-heparin procedure, as was seen in the present study. 7 Another report showed that platelet aggregability increased during RF current delivery, 9 and Manolis et al showed that RF-CA provoked an elevation in the D-dimer concentration by 48 h after the procedure.…”
Section: Thrombogenesis Caused By Radiofrequency Currentsupporting
confidence: 67%
See 1 more Smart Citation
“…The hemostasis that occurs with the placement of catheters has been described, 6,7,16,17 with some investigators correlating it with the duration of the pre-heparin procedure, as was seen in the present study. 7 Another report showed that platelet aggregability increased during RF current delivery, 9 and Manolis et al showed that RF-CA provoked an elevation in the D-dimer concentration by 48 h after the procedure.…”
Section: Thrombogenesis Caused By Radiofrequency Currentsupporting
confidence: 67%
“…According to our results, the elevation of the D-dimer concentration reported by Manolis et al might represent the delayed phase, but comparison of the present and previous studies depends on the anticoagulation regimen, including the administration of heparin and low molecular weight heparin. 7,8,17 …”
Section: Thrombogenesis Caused By Radiofrequency Currentmentioning
confidence: 99%
“…The benefit of heparinization administration during catheter ablation procedures is unclear, with several reports demonstrating either no benefit or no enhanced benefit with earlier heparin administration after placement of sheaths. 544,556,557 Epstein et al 558 demonstrated a low incidence of embolic complications among 758 pediatric and congenital patients from 11 centers. A wide variety of anticoagulation protocols was used, but all used heparin for left-side ablations.…”
Section: Anticoagulation and Catheter Ablation Proceduresmentioning
confidence: 99%
“…Third, LACA induces an immediate systemic activation of platelets and of the coagulation system. 31,32 Fourth, despite a high spontaneous closure rate, the trans-septal puncture may leave a persisting atrial septal defect even after 6 months, 33 opening the door for paradoxical embolism. Fifth, periprocedural cardioversion may increase the risk of thrombus formation, 23,34 but available data are inconsistent.…”
Section: Potential Mechanisms Of Laca-associated Strokementioning
confidence: 99%